IMPLEMENTASI KEBIJAKAN IDENTITAS KEPENDUDUKAN DIGITAL (IKD) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUKABUMI - Melani, Arie Melani Purbasari (Jurnal Dialektika Politik, 2025)
Digital Population Identity (IKD) is electronic information used to represent Population Documents and return data in digital applications via devices that display Personal Data as the identity in question. The aim of this research is to determine the implementation of the Digital Population Identity (IKD) Policy at the Sukabumi Regency Population and Civil Registration Service. The theory used in this research is: Interests influenced by the existence of the program, type of benefits to be generated, scope of desired change, position of decision maker, program implementer, and resources provided. (Grindle in Anggara (2018:255))This research uses a qualitative approach with descriptive methods. Data were collected through participatory and active observation, semi-structured interviews and documentation using notebooks, cameras and recordings. Validate the information data that has been collected by testing credibility through triangulation (technique, source and time) and analysis using reduction techniques, presenting data and drawing conclusions. Setting Informants used purposive sampling and snowball sampling methods, there were 5 informants in this study, namely: 1 Service Secretary, 1 Head of Division, 1 Service, 2 Community. The results of this research, seen from the aspect of interests influenced by the program, are appropriate, seen from the aspect of the types of benefits that will be produced are quite appropriate, seen from the aspect that the range of changes desired is quite optimal. seen from the aspect that the position of the decision maker is not adequate, seen from the aspect that the program implementer is not optimal, and seen from the aspect that the resources provided are quite adequate.